Implementation On Regulation Of Ministry Of Health Number 21 Of 2013 About Prvention Of HIV/AIDS In Work Area Of Talise Public Health Center In Mantikulore Subdistric - Magvira, Rheina (Tadulako University, 2020)
Based on data of Health Office of Palu City in 2019 about HIV/AIDS cases, it reached 818 cases of HIV and 306 cases of AIDS, and 109 of sufferers died. The highest cases of HIV/AIDS were in Talise Public Health Center with 13 of HIV. The factor that causes the highest number of HIV/AIDS cases in Talise Public Health Center is the lack of patients participation in counseling, mobile VCT, and many of them do not follow the instruction of Public Health Center in conducting the treatment to the patients of HIV/AIDS. Another factor is the lack of human resources as counselors and lab staff, there is no special room for HIV/AIDS patients inside or outside the Health Center, and there is no incentive provided by the Health Center for the field workers. This study aims to describe the Implementation on Regulation of Ministry of Health Number 21 of 2013 about HIV/AIDS Prevention in work area of Talise Public Health Center, Mantikulore Subdistrict. The study applied qualitative research using a case study approach. Technique of selecting the informants was purposive sampling. There were 6 informants, nameley key informant (Head Of Public Health Center). Ordinary informants (HIV/AIDS program holders), and additional informants were HIV/AIDS patients. Data collection techniques were through triangulations: indept interview, observation and ducumentation using interview guidelines. The result of the study shows that communication is one of an obstacle. Many patients are shy and do not want to take part in examining the reproductive organs. Therefore, they do not receive the status as PLHIV patient. Resources and disposition are not good enough because health center does not allocate addition staff as well as rewards to officers, the budget only for operational, the bureaucratic structure is good enough, and the cross-sector role is supportive. It is expected that Talise Publich Health Center can improve more about the management and standards releted to the Regulation of Ministry of Health Number 21 of 2013 concerning the tackling of HIV/AIDS.